Perancangan Buku Pedoman Pelaksanaan Didikan Subuh Di Desa Tanjung Pucuk Jambi Kabupaten Tebo - Keken Parmita; Supriadi Supriadi; Jasmienti Jasmienti; Fauzan Fauzan (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
This research is motivated by several problems that the authors found in the activities of implementing dawn education in Tanjung Pucuk Village, Jambi, Tebo Regency, to be precise in the Al-Muhajirin Mosque. The dawn education activities have not been carried out perfectly, due to the absence of proper guidelines for carrying out the dawn education activities, the dawn education teachers are often confused in carrying out the dawn education activities. In each dawn education activity there is only the activity of reading short surahs after the dawn prayer alternately, so that the dawn education activities are not interesting for the dawn students. The purpose of this study was to produce a manual for the implementation of dawn education that can be used in general in Tanjung Pucuk Jambi Village, Tebo Regency, specifically in the Al-Muhajirin Mosque, which is valid, practical, and effective for application in dawn education activities. The type of research used is Research and Development or abbreviated as R&D. The R&D model used is the Four D (4-D) version from Thiagarajan (Define, Design, Develov, Disseminate). From the results of the research that has been done, it can be concluded that the produced Subuh Education Manual can be used and is suitable for use as a guide for teachers and students who carry out their special Subuh education activities in Jambi. The results of the validation trial by experts on the subuh education guidebook are categorized as valid with an average value of 0.81. The practicality test of the subuh education manual showed that the manual had a very high level of practicality with a value of 0.95. And the results of the manual effectiveness test have a moderate level of effectiveness with a value of 0.4.